PENDAPATAN RUMAH TANGGA PETANI KAKAO DI DESA PESAWARAN INDAH KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN - Gusti J, Ayu Indah; Haryono, Dwi; Prasmatiwi, FE (Jurnal Ilmu-Ilmu Agribisnis, 2013)
The purposes of this research were to analyze cocoa farmer household income,income distribution, and land distribution. This research was conducted at Pesawaran Indah village of Padang Cermin subdistrict of Pesawaran Regency using a survey method. Respondents of 46 cocoa farmers were chosen by using a stratified random sampling. The research results showed that cocoa farmer household income in Pesawaran Indah Village was Rp18,790,360.70/year, 76.02 percent (Rp14,285,143.31/year) of which came from cocoa farm operations, 23.10 percent (Rp4,340,869.57/year) from other farm operation, and 0.87 percent (Rp164,347.83/year) from farm operation activity other than cocoa.Â  The distribution of cocoa farmer household income was inequitable, showed by number of Gini Ratio of 0.46 (Oshima) or an imbalance medium position.Â  Cocoa farmer land distribution was equitable with Gini index values of 0.36 (Oshima) and 1.07 (World Bank).Key words : household income, prosperity grade, the distribution income, cocoa and gini ratio